Analisis Kepatuhan Wajib Pajak Yang Dipengaruhi Oleh Kualitas Pelayanan Pajak, Tarif Pajak, Dan Sanksi Pajak - Nugraha, Shofiah Cahyani; Febriansyah, Angky (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
This study aims to examine and analyze Taxpayer Compliance which is influenced by Tax Service Quality, Tax Rates, and Tax Sanctions case study at the Tax Service Office (KPP) Cicadas Bandung. The method used in this study is a descriptive and verifiative method using the SmartPLS 4.0 application. The unit of analysis in this study is Individual Taxpayers at KPP Cicadas Bandung totaling 100 respondents, the sampling technique used is random sampling. The results showed that the quality of tax services did not have a significant effect on taxpayer compliance with KPP Cicadas Bandung. Likewise, the tax rate, which also does not have a significant effect on taxpayer compliance with KPP Cicadas Bandung. However, tax sanctions have proven to have a significant effect on the level of taxpayer compliance with KPP Cicadas Bandung.